Analysis of the current situation of the fodder base in the cows in Latakia Governorate - دخيل, صفاء (Submission and Review of Research -Biological Sciences Series, 2025)
This research aims to study the economic status of the fodder base in the dairy cow sector in Latakia Governorate and to examine the impact of using alternative fodder on production costs and milk yield. The study employed a descriptive-analytical approach, using data collected through a questionnaire distributed to a random sample of 385 breeders from various regions of the governorate. Data were analyzed using SPSS and Excel, with both descriptive and inferential statistical tests applied. The results showed that 75.3% of breeders used modern balanced fodder alongside traditional types. The average feeding cost in private farms was found to be 58–70% lower than that of traditional breeders. Additionally, milk yield in private farms was 25% higher. The study recommends adopting strategies to locally produce modern balanced fodder and improve its efficient use in cow feeding systems.